(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article substantiates the importance of considering the sociolinguistic component of communicative competence in the educational process of student training. Special attention is given to the historical and linguistic component of studying the Ukrainian language, which plays a crucial role in developing students’ linguistic, historical, and political awareness. It helps them comprehend the evolution of their native language, its forms of existence, and its significance in society, contributing to the formation of Ukrainian identity, the preservation of historical memory, and the cultivation of an understanding of the necessity to protect and develop the Ukrainian language. The authors of the article propose ways to integrate the historical and linguistic aspect, particularly the issue of linguicide, into the curriculum of the educational component "Speech Culture and Business Communication." They present a list of historical and linguistic components and topics within the course syllabus that ensure their coverage. The article provides a list of individual tasks for students aimed at researching the historical and linguistic component "On the Facts of Linguicide of the Ukrainian Language and Oppression of Ukrainians (Formation of Historical Memory Through Language History)." These tasks include watching documentary and feature films, familiarizing themselves with social projects on linguicide, analyzing author-created YouTube videos about linguicide, engaging in project work, and applying interactive approaches. The integration of the historical-linguistic component into the educational process can be implemented through organizing excursions (both real and virtual) to museums, libraries, and research institutions, watching documentary and feature films, conducting discussion-based lessons, lectures, text analysis, and other activities. The historical and linguistic component of studying the Ukrainian language significantly influences the development of both linguistic competence and national consciousness among students.